2013
DOI: 10.1186/1471-2377-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Australian Cerebral Palsy Child Study: protocol of a prospective population based study of motor and brain development of preschool aged children with cerebral palsy

Abstract: BackgroundCerebral palsy (CP) results from a static brain lesion during pregnancy or early life and remains the most common cause of physical disability in children (1 in 500). While the brain lesion is static, the physical manifestations and medical issues may progress resulting in altered motor patterns. To date, there are no prospective longitudinal studies of CP that follow a birth cohort to track early gross and fine motor development and use Magnetic Resonance Imaging (MRI) to determine the anatomical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
115
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 78 publications
3
115
0
1
Order By: Relevance
“…Children were ineligible if they had an uncontrolled seizure disorder. They were identified from a research database of children born in Queensland attending state-wide CP health services as described in the Australian CP Child Study protocol 23 and in the protocol for this study. 21 Identification of children for inclusion in the research database followed the guidelines of the Surveillance of Cerebral Palsy in Europe 24 and used a working definition of CP as a motor impairment stemming from an early, non-progressive brain lesion.…”
Section: Group With Unilateral Cpmentioning
confidence: 99%
“…Children were ineligible if they had an uncontrolled seizure disorder. They were identified from a research database of children born in Queensland attending state-wide CP health services as described in the Australian CP Child Study protocol 23 and in the protocol for this study. 21 Identification of children for inclusion in the research database followed the guidelines of the Surveillance of Cerebral Palsy in Europe 24 and used a working definition of CP as a motor impairment stemming from an early, non-progressive brain lesion.…”
Section: Group With Unilateral Cpmentioning
confidence: 99%
“…In Australia, there are no intervention programmes available to promote social, communication, and cognitive skill development. In the Australian CP Child Study, 16 we monitored by formal questionnaire the use of all medical and allied health services and therapeutic recreational programmes that these children accessed every 6 months; we can confirm the lack of specific, tailored interventions to improve communication, social functioning, and cognition for children with CP. In Australia, we acknowledge that children with CP may access generic early child development programmes in their fourth year, provided by specialist, trained teachers, in the form of play-based programmes for 3 to 6 hours per week before starting formal schooling (30h per week) from the age of 5 years.…”
mentioning
confidence: 99%
“…7,8 When considering each school-readiness domain individually, the literature has demonstrated that in 5-year-old children with CP half present with one or more activity limitations in oromotor function and/or communication 13 and 16% are non-verbal. 13,14 Cohort studies of preschoolage children with CP have also addressed the domains of physical performance across the spectrum of severity in self-care 16 and social functioning. 15 There is a paucity of cross-sectional data in this age group about cognitive skills and general knowledge.…”
mentioning
confidence: 99%
See 2 more Smart Citations